Not All Traumas Are Equal: Post-Traumatic Stress and Quality of Life among Women in Prison - Prost, Stephanie Grace (Women & criminal justice, 2022)
Measures of well-being have gained importance in criminal justice. Examining the relationship between interpersonal traumatic experiences, post-traumatic stress (PTS), and quality of life (QOL) is thus an essential contribution to existing literature. Using data from interviews conducted with a sample of women incarcerated in a U.S. state prison (n = 83), we examined differences in PTS and QOL between groups of women who did and did not report experiences of captivity, sexual assault, and other, unwanted sexual experiences. We also explored relationships between these experiences, PTS, and QOL. Women with any of these traumatic experiences reported higher PTS than their non-affected peers and women who were held captive prior to incarceration had the highest levels of PTS and the lowest levels of environmental QOL. We also found relationships between captivity, financial security, and PTS. Systems-oriented implications for correctional and community settings are discussed.